Child-Friendly School-Based Character Education Strategy in Realizing the Well-Being of Inclusive Students in Elementary Schools - Indriani, Fitri; Hastuti, Dwi; Tumiran, Mohd Amzari (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study aimed to explore the strategy of character education based on Child-Friendly Schools (SRA) in realizing the well-being of inclusive students in elementary schools. This study used a qualitative approach with a case study design. The research location was at State Elementary School Giwangan, Yogyakarta City, which applies the principles of inclusivity and the values of child-friendly schools (SRA) in an integrated manner. This study used a qualitative approach with a case study design. Data collection techniques were carried out through in-depth interviews, non-participatory observations, and documentation, involving the principal, class teachers, special assistant teachers (GPK), and inclusion students. The data was analyzed using data reduction analysis techniques, data presentation, and a conclusion drawn, accompanied by triangulation of sources to ensure the validity of the data. The results of the study showed five main strategies: (1) internalization of character values through daily activities and examples; (2) adaptive character learning by teachers and GPK with the help of visual media and personal mentoring; (3) collaborative planning between stakeholders to ensure inclusive character programs; (4) the active involvement of inclusion students in various character building activities in schools; and (5) the provision of a physical and social environment that supports the emotional and social well-being of students. This strategy has been shown to encourage inclusive participation, foster empathy, and strengthen students' sense of belonging to the school. This research contributed to the development of inclusive character education by emphasizing the practical and holistic application of child-friendly values in elementary schools. These findings offer a valuable framework for schools in building an educational culture that is humane, inclusive, and supports the growth and development of all students.